2020
DOI: 10.5194/acp-2020-1223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photo-degradation of atmospheric chromophores: type conversion and changes in photochemical reactivity

Abstract: Abstract. Atmospheric chromophoric organic matters (COM) can participate in photochemical reactions because of the photosensitiveness, thus COM have a potential contribution to aerosols aging. The photochemical mechanism of atmospheric COM and the effect of photo-degradation on its photochemical reactivity are not fully understood. To address this knowledge gap, the characteristics of COM photo-degradation and the potential effects of COM photolysis on the photochemical reactivity are illustrated. COM are iden… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…The complexation of different metal ions had significant effects and differences on the production of 3 HULIS*. As shown in Figure S9, atmospheric HULIS (about 17 mg·C·L –1 ) stressed by four metal ions (100 and 250 μmol·L –1 ), Zn 2+ , Al 3+ , Cu 2+ , and Fe 3+ , showed a gradual increase in cumulative triplet-state production with the increase of light radiation duration, which was similar to previous studies by Mu et al , Cu 2+ , Zn 2+ , and Al 3+ -coupled systems have decreased 64, 26, and 28% of the cumulative triplet-state generation in the atmospheric HULIS (0 min of light radiation), respectively. Also, with the increase of metal ion concentration, the inhibitory effect increased slightly, which was negligible.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The complexation of different metal ions had significant effects and differences on the production of 3 HULIS*. As shown in Figure S9, atmospheric HULIS (about 17 mg·C·L –1 ) stressed by four metal ions (100 and 250 μmol·L –1 ), Zn 2+ , Al 3+ , Cu 2+ , and Fe 3+ , showed a gradual increase in cumulative triplet-state production with the increase of light radiation duration, which was similar to previous studies by Mu et al , Cu 2+ , Zn 2+ , and Al 3+ -coupled systems have decreased 64, 26, and 28% of the cumulative triplet-state generation in the atmospheric HULIS (0 min of light radiation), respectively. Also, with the increase of metal ion concentration, the inhibitory effect increased slightly, which was negligible.…”
Section: Resultssupporting
confidence: 88%
“…Brown carbon (BrC) aerosols, which can absorb near-ultraviolet and visible light, are important contributors to the radiative forcing and the greenhouse effect in the troposphere . As an important component of BrC, humic-like substances (HULIS) can also produce active intermediates, such as triplet organics and reactive oxygen species (ROS) via photochemistry, ,, and further initiate the aging process of organic aerosols in the particle phase. For example, it has been found that triplet organics can oxidize isoprene and induce a portion of ROS, such as hydroxyl radical ( · OH), single oxygen ( 1 O 2 ), and superoxide (O 2 ·– ). , The atmospheric concentrations of HULIS, which mainly originated from terrestrial biomass burning (11–36%) and coal combustion (11–41%), are in the range of 0.39–13.4 μg·m –3 in China. …”
Section: Introductionmentioning
confidence: 99%
“…The experimental results show that 3 C* plays a leading role in the production of 1 O2 and • OH. When there are triplet substances in the environment, the triplet state transfers energy to O2 molecules to form 1 O2, and 1 O2 may undergo complex reactions to generate • OH (Chen et al, 2020;Mu et al, 2020). In this study, the genertation mechanism of • OH varies with the components.…”
Section: Ros Generation Caused By 3 C*mentioning
confidence: 88%